Effect of Capital Constraint in a Dual-Channel Supply Chain - Lang Xu; Jia Shi; Jihong Chen (Complexity)
Capital constraint is a significant factor that mainly restricts the development of small- and medium-sized enterprises. This paper explores the channel strategy and pricing decision in a dual-channel supply chain, which consists of one supplier and one retailer. Adequate and inadequate capital constraints for the supplier are distinguished by determining whether open the retail channel to sell. The observations offer managerial insights into supply chain member. First, the results indicate that the capital constraint is a key factor affecting channel strategies and pricing decisions. With the increased value of capital constraint, the wholesale price of offline channel and the selling price of online channel firstly decrease and then remain constant. Second, the results demonstrate that, with capital constraint, the supplier pays more attention to consumers’ brand loyalty if it chooses to open the online channel only. Additionally, the price-sensitivity parameter has no effect on the strategy of opening only the offline channel. Moreover, when the channel competition is too intense, the supplier will choose to only open the online channel strategy and increase the online selling price if the capital is insufficient.